Glyndŵr's Rebellion, the Bishop of Bangor and the Councils of Pisa and Constance. (1st December 2016) - Frame, Paul
The Great Schism in the medieval church between 1378 and 1417 ultimately saw three popes reign at the same time. During the years of Owain Glyndŵr's rebellion (1400–c.1421), two church councils aimed at ending the schism took place: one at Pisa in 1409 and the other at Constance (now Konstanz in Germany) from 1414 to 1418. Evidence suggesting a Welsh presence at these councils is presented here, together with a discussion of the possible significance of that presence for our understanding of the ecclesiastical and political history of the later stages of Glyndŵr's rebellion (1406–c.1421). The complex history of the see of Bangor, which during this period had three possible bishops, is also explored.